2015
DOI: 10.1186/s12917-015-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of recent foot-and-mouth disease viruses from African buffalo (Syncerus caffer) and cattle in Kenya is consistent with independent virus populations

Abstract: BackgroundUnderstanding the epidemiology of foot-and-mouth disease (FMD), including roles played by different hosts, is essential for improving disease control. The African buffalo (Syncerus caffer) is a reservoir for the SAT serotypes of FMD virus (FMDV). Large buffalo populations commonly intermingle with livestock in Kenya, yet earlier studies have focused on FMD in the domestic livestock, hence the contribution of buffalo to disease in livestock is largely unknown. This study analysed 47 epithelia collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
3
24
0
3
Order By: Relevance
“…FMDV can be divided into seven serotypes (O, A, C, SAT 1, SAT 2, SAT3, and Asia 1) (Kitching et al, 1989), with no cross-immunity between serotypes (Kitching et al, 1989). In Kenya, FMDV was first described in 1952, with serotypes O, A, SAT 1 and SAT 2 presently circulating in the country (Wekesa et al, 2015b) and generally in East Africa (FAO., 2016, Sangula et al, 2011. A Bayesian phylogenetic analysis of SAT1 serotypes from Kenya revealed two independent introductions from southern Africa (Sangula et al, 2010); with that buffalo are maintenance hosts for SAT serotypes of FMDV, and proximity to wildlife areas is a risk factor for clinical outbreaks in cattle in East Africa (Ayebazibwe et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMDV can be divided into seven serotypes (O, A, C, SAT 1, SAT 2, SAT3, and Asia 1) (Kitching et al, 1989), with no cross-immunity between serotypes (Kitching et al, 1989). In Kenya, FMDV was first described in 1952, with serotypes O, A, SAT 1 and SAT 2 presently circulating in the country (Wekesa et al, 2015b) and generally in East Africa (FAO., 2016, Sangula et al, 2011. A Bayesian phylogenetic analysis of SAT1 serotypes from Kenya revealed two independent introductions from southern Africa (Sangula et al, 2010); with that buffalo are maintenance hosts for SAT serotypes of FMDV, and proximity to wildlife areas is a risk factor for clinical outbreaks in cattle in East Africa (Ayebazibwe et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, buffalo in South Africa are largely separated from cattle by fencing (Dion et al, 2011, Miguel et al, 2013, which is in stark contrast to the extensive wildlife-livestock sympatry observed in semi-arid pastoralist rangelands in East Africa. Only SAT1 and 2 serotypes have been isolated from buffalo in Kenya, and the single sequences available each for buffalo-origin SAT1 and SAT2 viruses are genetically distinct from those in livestock, leading to the theory of independent virus populations in East African buffalo and cattle (Wekesa et al, 2015b). However, more genetic data on sequences found in buffalo are needed to elucidate the molecular epidemiology of FMDV in East African wildlife-livestock interfaces and the phylogenetic relationship between buffalo-derived viruses and vaccine strains.…”
Section: Introductionmentioning
confidence: 99%
“…Hedger et al [27] found that animals undergoing natural infection with one type of FMDV (type O) had equal or even higher serum antibody titres against one or more of the other types tested (types A, C, Asia 1 and SAT 1). Thus, it remains unclear whether the cross-reactivity among serotypes is caused by low assay specificity, or heterotypic humoral responses following virus infections [28]. Though cross–reactivity among FMDV serotypes is undesirable, it is preferable when sensitivity is the aim.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of FMDV phylogenetics have been published in the past 5 years (Ahmed et al, 2012;Gorna et al, 2014;Kasanga et al, 2015;Parthiban et al, 2015b;Subramaniam et al, 2015;Wekesa et al, 2015;Zhang et al, 2015). At a basic level, these studies can identify related outbreaks and should form part of routine surveillance; they may also indicate the extent of relatedness between vaccine and field strains.…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%